A Novel Theanine Complex, Mg-L-Theanine Improves Sleep Quality via Regulating Brain Electrochemical Activity - Dasdelen, Muhammed Furkan; Er, Sezgin; Kaplan, Berkan; Celik, Suleyman; Beker, Mustafa Caglar; Orhan, Cemal; Tuzcu, Mehmet; Sahin, Nurhan; Mamedova, Havakhanum; Sylla, Sarah; Komorowski, James; Ojalvo, Sara Perez; et al. (Frontiers in Nutrition, 2022)
L-theanine is commonly used to improve sleep quality through inhibitory neurotransmitters. On the other hand, Mg2+, a natural NMDA antagonist and GABA agonist, has a critical role in sleep regulation. Using the caffeine-induced brain electrical activity model, here we investigated the potency of L-theanine and two novel Mg-L-theanine compounds with different magnesium concentrations on electrocorticography (ECoG) patterns, GABAergic and serotonergic receptor expressions, dopamine, serotonin, and melatonin levels. Furthermore, we evaluated the sleep latency and duration in the pentobarbital induced sleep model. We herein showed that L-theanine, particularly its various complexes with magnesium increases the expression of GABAergic, serotonergic, and glutamatergic receptors, which were associated with decreased ECoG frequency, increased amplitude, and enhanced delta wave powers. Besides increased dopamine, serotonin, and melatonin; decreased MDA and increased antioxidant enzyme levels were also observed particularly with Mg-complexes. Protein expression analyses also showed that Mg-L-theanine complexes decrease inducible nitric oxide synthase (iNOS) and endothelial nitric oxide synthase (eNOS) levels significantly. In accordance with these results, Mg complexes improved the sleep latency and duration even after caffeine administration. As a result, our data indicate that Mg-L-theanine compounds potentiate the effect of L-theanine on sleep by boosting slow-brain waves, regulating brain electrical activity, and increasing neurotransmitter and GABA receptor levels.